Architecture & contruction - Safran Pete; Glossbrenner, Alfred; Cambridge Educational (New Jersey : Cambridge Educational, 2004)
With over 13 million jobs in the US alone, this program offers a sense of how wide-ranging the opportunities can be by looking at the educational and training requirements as well as the actual work of an architect, plumber, electrician, construction personnel and a building inspector.
Camera, Bob Sullivan ; editor, Bob Suravage.
Narrator, Jeannie Stith.
DVD format.
Keywords: Architecture -- Vocational guidance; Plumbing -- Vocational guidance; Electricians -- Vocational guidance; Building inspectors -- Vocational guidance